Lyn, Lupus, and (B) Lymphocytes, a Lesson on the Critical Balance of Kinase Signaling in Immunity - Brodie, Erica J.; Infantino, Simona; Low, Michael S. Y.; Tarlinton, David M. (Frontiers in Immunology, 2018)
Systemic Lupus Erythematosus (SLE) is a progressive autoimmune disease characterised by increased sensitivity to self-antigens, auto-antibody production and systemic inflammation. B cells have been implicated in disease progression and as such represent an attractive therapeutic target. Lyn is a Src-family tyrosine kinase that plays a major role in regulating signalling pathways within B cells as well as other hematopoietic cells. Its role in initiating negative signalling cascades is especially critical as exemplified by Lyn-/- mice developing an SLE-like disease with plasma cell hyperplasia, underscoring the importance of tightly regulating signalling within B cells. This review highlights recent advances in our understanding of the function of the Src-family tyrosine kinase Lyn in B lymphocytes and its contribution to positive and negative signalling pathways that are dysregulated in autoimmunity